Atovaquone/Proguanil Resistance in an Imported Malaria Case in Chile - Chenet, Stella M. (Am J Trop Med Hyg, 2021)
In November 2018, we diagnosed a cluster of falciparum malaria cases in three Chilean travelers returning from Nigeria. Two patients were treated with sequential intravenous artesunate plus oral atovaquone/proguanil (AP) and one with oral AP. The third patient, a 23-year-old man, presented with fever on day 29 after oral AP treatment and was diagnosed with recrudescent falciparum malaria. The patient was then treated with oral mefloquine, followed by clinical recovery and resolution of parasitemia. Analysis of day 0 and follow-up blood samples, collected on days 9, 29, 34, 64, and 83, revealed that parasitemia had initially decreased but then increased on day 29. Sequencing confirmed Tyr268Cys mutation in the cytochrome b gene, associated with atovaquone resistance, in isolates collected on days 29 and 34 and P. falciparum dihydrofolate reductase mutation Asn51Ile, associated with proguanil resistance in all successfully sequenced samples. Molecular characterization of imported malaria contributes to clinical management in non-endemic countries, helps ascertain the appropriateness of antimalarial treatment policies, and contributes to the reporting of drug resistance patterns from endemic regions.